Sustainable urban design with industrial and agro-industrial influence in the El Palaciero community of Lara State (Gaceta Técnica, 2026)
This research aims to propose a sustainable urban design for areas undergoing transformation and new development, with industrial and agro-industrial influence, in the El Palaciero community in Lara State, Venezuela. This community is relevant because it has high development potential due to its location within the immediate urban environment of the Palavecino Special Economic Zone. To achieve this objective, a physical, social, and environmental diagnosis of the study area was conducted using direct observation and a comprehensive literature review, which together form the theoretical basis. The information gathered allowed for the identification of strategic guidelines oriented toward fulfilling the Sustainable Development Goals and the proposal of best practices with action lines established in the sustainable urban design framework for the El Palaciero community. The ultimate goal is to serve as a guiding model for the development of other communities with similar characteristics
Keywords: urban development; urban planning; sustainable design; El Palaciero